Análisis semiótico de la imagen en la comprensión de pósteres de películas del género drama en el cine ecuatoriano periodo 1990-2010 - Sailema Aguagallo, Andrés Gustavo (2025)
This research analyzes the visual imagery in posters of Ecuadorian drama films (1990- 2010) using a semiotic approach. Its objective is to assess the level of comprehension of these posters by identifying the visual signs present and their impact on audience perception. The study is based on Charles Sanders Peirce's semiotic theory, classifying signs into icons, indexes, and symbols to understand how they construct meaning and convey emotions. A mixed-methods approach is employed, combining semiotic analysis, interviews with experts in film and graphic design, and an eye-tracking study to validate the findings. The results highlight that visual signs in Ecuadorian film posters show recurring patterns in color usage, typography, and composition, influencing the interpretation of the drama genre. However, opportunities for improvement are identified in terms of message clarity and emotional connection with the audience. As a recommendation, graphic designers and filmmakers are encouraged to integrate semiotic analysis into the poster design process to enhance their impact. Additionally, conducting preliminary studies on audience preferences is emphasized to better align visual elements with their expectations. In conclusion, this study provides valuable insights into visual communication in Ecuadorian cinema, offering strategies for more effective poster design to strengthen the identity and commercialization of the country’s drama films.